Investigating the effect of rTMS over the temporoparietal cortex on the Right Ear Advantage for perceived and imagined voices - Giulia Prete; Benedetta Rollo; Rocco Palumbo; Irene Ceccato; Nicola Mammarella; Alberto Di Domenico; Paolo Capotosto; Luca Tommasi (Scientific Reports)
Abstract A Right Ear Advantage (REA) is well-established in perceptual tasks but it has been found also during imagery. It is ascribed to the left temporoparietal activity for language, and it can be absent/reversed in some clinical conditions including auditory hallucinations. We applied 1-Hz repetitive TMS over TP3/TP4 (left/right language areas) identified through neuronavigation in 18 healthy participants, before administering a modified white noise (WN) speech illusion paradigm: a voice was presented at one ear, at the same or lower intensities with respect to binaural WN. In some trials the voice was not presented, but participants were anyway instructed to report in which ear they believed perceiving it in all trials. Results confirmed the REA both when the voice was present (perceptual REA) and when it was absent (imaginative REA). Interestingly, results suggested that the correct localization of the voice when the stimulus was ambiguous (presented at low intensity and “masked” by WN) was better when TMS was applied over the right/left hemisphere, in male participants with a low/high proneness to unusual experiences (e.g., auditory hallucinations), respectively. This interaction must be further explored to shed light on the relationship between hemispheric asymmetries and auditory hallucinations, in healthy and clinical samples.